2012
DOI: 10.1115/1.4006566
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Steady Performance of Double-Entry and Twin-Entry Turbocharger Turbines

Abstract: Most boosting systems in internal combustion engines utilize “pulse turbocharging” to maximize the energy extraction by the turbine. An internal combustion engine with more than four cylinders has a significant overlap between the exhaust pulses which, unless isolated, can decrease the overall pulse energy and increase the engine pumping loss. Thus, it is advantageous to isolate a set of cylinders and introduce the exhaust gases into two or more turbine entries separately. There are two main types of multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…Some engine manufacturers choose twin-entry turbines (where the turbine scroll is meridionally divided, as shown in Figure 1a); others opt for the dual-volute turbine (turbine scroll is circumferentially divided, as shown in Figure 1b). The comparison of performance parameters between these two types of double entry turbines has been extensively discussed since Pischinger and Wunsche [10] until more recently, such as in the work by Romagnoli et al [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some engine manufacturers choose twin-entry turbines (where the turbine scroll is meridionally divided, as shown in Figure 1a); others opt for the dual-volute turbine (turbine scroll is circumferentially divided, as shown in Figure 1b). The comparison of performance parameters between these two types of double entry turbines has been extensively discussed since Pischinger and Wunsche [10] until more recently, such as in the work by Romagnoli et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the complete unequal admission maps are not always available because many gas stands are not capable of operating in those conditions. Addressing this, Romagnoli et al [11] proposed a map-based method for predicting the partial and unequal admission flows in double entry turbines (both twin and dual) from a given full admission map. Based on the experimental data, two correlations were proposed, one for twin-entry and another for a dual-volute turbine, and they concluded that the twin-entry turbine characteristic agreed reasonably well with their approach.…”
mentioning
confidence: 99%
“…In a double entry configuration the inlets create two separated admission channels which feed different sectors of the rotor in circumferential direction. In twin scroll 2 International Journal of Rotating Machinery turbines the inlet is meridionally divided into two limbs (hub and shroud rotor sides), but in this case both of them feed the entire rotor circumference [5].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Dale and Watson [6] experimentally demonstrate that, even if the two limbs of a twin scroll turbine are symmetrical and the mass flow rates from inlets are almost coincident, highest values of efficiency are reached when the shroud limb flow rate is greater than the one passing through the hub branch. Several works also investigate turbines performances under steady and unsteady flow conditions [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…By using a twin-entry radial inflow turbine there is a better recovery of energy inducted alternatively and intermittently into the hub and shroud entries of the volute, and subsequently the dynamic pressure of exhaust gas flow pulses is used effectively. Romagnoli et al [1] compared between the steady performances of two types of turbines, double-entry and twin-entry, and showed that, in the case of a twin-entry turbine, the interaction between entries is significant and causes the flow capacity to be larger than that which would be obtained by halving the mass flow in full admission, in contrast to a double-entry turbine. Pischinger and Wunsche [2] studied the interaction between the inlet gas flows from comparable double-entry and twin-entry volutes under steady conditions.…”
Section: Introductionmentioning
confidence: 99%